Quenching of single-particle strength inferred from nucleon-removal transfer reactions on 15C - Y.C. Jiang; J. Chen; B.P. Kay; C.R. Hoffman; T.L. Tang; I.A. Tolstukhin; M.R. Xie; J.G. Li; N. Michel; M.L. Avila; Y. Ayyad; D. Bazin; et al. (Physics Letters B)
The difference in the proton and neutron separation energies (ΔS) of the weakly bound 15C ground state is -19.86 MeV, an extreme value. Data from intermediate-energy heavy-ion induced (HI-induced) knockout reactions on nuclei spanning −20≲ΔS≲+20 MeV, suggest that the degree to which single-particle strength is quenched, Rs, has a negative correlation with ΔS, decreasing from unity around −20 MeV to around 0.2 at +20 MeV. For the 15C ground state (Rs=0.96(4) in HI-induced knockout), contrasting results have recently been obtained via the neutron-adding transfer reaction, which reveal a value of Rs=0.64(15), similar to the value observed at modest ΔS and more extreme values of ΔS with reaction probes other than HI knockout. In order to explore the any potential differences between adding and removing processes in transfer reactions at extreme ΔS, single-neutron removal transfer reactions on 15C were performed at 7.1 MeV/u in inverse kinematics. The removal of a valence neutron in 2s1/2 orbit using both (p,d) and (d,t) reactions shows consistent quenching factors and agrees with those from the neutron-adding reaction. The present results, which can be compared with neutron knockout reaction, suggest that correlations, represented by the quenching factor, show limited dependence on neutron-proton asymmetry under the most extreme asymmetry conditions so far achieved in transfer reactions.